'EngNT' — Engineering live neural tissue for nerve replacement. Issue 5 (12th November 2021) - Phillips, James B.
Abstract : Peripheral nerve injury can result in severe long-term disability and current clinical approaches for repairing large gaps rely on the nerve autograft. Engineered Neural Tissue (EngNT) has been developed to provide living aligned therapeutic cells in a stabilised collagen hydrogel, mimicking the key features of the autograft. This Perspective article will introduce the field and discuss the current stage of translation, highlighting the key opportunities for commercial and clinical development.